Economic effects of overtime premium flexibility: Firm- and worker-level evidence from a law reform - Pedro S. Martins (Global Labor Organization (GLO), 2017)
In 2012, a new law allowed firms in Portugal to reduce the overtime premium paid by half. Until then, as in other countries, premiums were subject to a minimum level. We analyse matched panel data, including worker-level (base and overtime) hours and pay, to study the effects of the resulting greater flexibility in overtime pay setting. We find that half of the firms using overtime in 2011 did reduce their overtime premiums consistently with the reform, in particular firms making greater use of overtime and paying higher premiums. Using difference-in-differences matching and a long list of covariates, we also find that those firms that cut overtime premiums exhibit significant relative increases in overtime usage, employment and sales following the reform. Our results also highlight the important but not exclusive role of legal restrictions on downward nominal pay rigidity.
Keywords: J22; J23; J38; 330; Working time; wage rigidity; employment resilience; labour reforms